Corporate Governance Disclosure Index–Executive Pay Nexus: The Moderating Effect of Governance Mechanisms - Mohamed Elmagrhi (European Management Review, 2020)
This paper first employs principal component analysis technique to develop and introduce an alternative UK corporate governance disclosure index to the US-centric ones. Second, we then investigate whether this new corporate governance disclosure index can determine the level of executive pay (including CEOs, CFOs, and all executive directors) in UK listed firms, and consequently ascertain whether the governance mechanisms can moderate the pay-for-performance sensitivity. Employing data on corporate governance, executive pay and performance from 2008 to 2013, we find that, on average, better-governed firms, tend to pay their executives lower compared with their poorly-governed counterparts. Additionally, our findings suggest that the pay-for-performance sensitivity is generally positive, but improves in firms with high corporate governance quality, implying that the pay-for-performance sensitivity is contingent on the quality of internal governance structures. We interpret our findings within the predictions of optimal contracting theory and managerial power hypothesis.